2021
DOI: 10.1177/11206721211039337
|View full text |Cite
|
Sign up to set email alerts
|

Changes in ocular pulse amplitude and choroidal thickness in childhood obesity patients with and without insulin resistance

Abstract: Purpose: To compare choroidal thickness (CT) and ocular pulse amplitude (OPA) in childhood obesity with insulin resistance (IR) and without IR. Methods: Seventy-three childhood obesity and 62 healthy children, who were both age-matched and gender-matched, comprised the study population in this prospective study. Obesity was determined as having a body mass index (BMI) – standard deviation (SD) score that was > 2 SD. Intraocular pressure (IOP) and OPA were measured using a dynamic contour tonometer. The CT m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Interestingly CT measurements were thinner among those obese patients who did not have IR as compared to those with IR (36,51). The authors found a positive correlation between CT and HOMA-IR (36,51). Differences in CT values in obese with and without IR can be explained by the vascular action of insulin, which stimulates endothelial production of NO with subsequent choroidal vasodilation and increased CT (53).…”
Section: The Association Between Choroidal Thickness and Macular Reti...mentioning
confidence: 98%
See 3 more Smart Citations
“…Interestingly CT measurements were thinner among those obese patients who did not have IR as compared to those with IR (36,51). The authors found a positive correlation between CT and HOMA-IR (36,51). Differences in CT values in obese with and without IR can be explained by the vascular action of insulin, which stimulates endothelial production of NO with subsequent choroidal vasodilation and increased CT (53).…”
Section: The Association Between Choroidal Thickness and Macular Reti...mentioning
confidence: 98%
“…Elevated intraocular pressure (IOP) may irreversibly damage the optic nerve and could result in visual impairment and blindness (33). Many studies have supported the association between higher values of intraocular pressure and high BMI (34, 35) as well as obesity (36)(37)(38). Akinci et al have reported that the average IOP was significantly higher in obese children than in the control group; gender and age connections were not statistically significant between groups.…”
Section: Influence Of Childhood Obesity On Intraocular Pressurementioning
confidence: 99%
See 2 more Smart Citations
“…[11] Loureiro et.al found that choroidal thickness (CT) in temporal and inferotemporal sectors were signi cantly lower in MetS patients. [12] Factors pertinent to NAFLD including obesity, [13,14] cardiovascular risk factors [15] and insulin resistance [16] have also proven to be negatively correlated with CT. Even there is robust evidence suggesting lower CT in in ammatory vascular disease such as systemic lupus erythematosus [17] , behçet [18] , scleroderma [19] and so forth [20] .…”
Section: Introductionmentioning
confidence: 99%